181/1)
$\small \sqrt{\left(2+\dfrac{2}{3}\right)×\dfrac{11}{4}-\dfrac{2}{9}}= $
$\small =\sqrt{\left(\dfrac{6+2}{3}\right)×\dfrac{11}{4}-\dfrac{2}{9}}= $
$\small =\sqrt{\dfrac{\cancel8^2}{3}×\dfrac{11}{\cancel4_1}-\dfrac{2}{9}}= $
$\small =\sqrt{\dfrac{2}{3}×\dfrac{11}{1}-\dfrac{2}{9}}= $
$\small =\sqrt{\dfrac{22}{3}-\dfrac{2}{9}}= $
$\small =\sqrt{\dfrac{66-2}{9}}= $
$\small =\sqrt{\dfrac{64}{9}}= \dfrac{8}{3}$
181/2)
$\small \sqrt{\left(\dfrac{5}{6}+\dfrac{1}{2}-\dfrac{1}{4}\right)×\dfrac{9}{26}+\dfrac{3}{16}}=$
$\small =\sqrt{\left(\dfrac{10+6-3}{12}\right)×\dfrac{9}{26}+\dfrac{3}{16}}=$
$\small =\sqrt{\dfrac{\cancel{13}^1}{\cancel{12}_4}×\dfrac{\cancel9^3}{\cancel{26}_2}+\dfrac{3}{16}}=$
$\small =\sqrt{\dfrac{1}{4}×\dfrac{3}{2}+\dfrac{3}{16}}=$
$\small =\sqrt{\dfrac{3}{8}+\dfrac{3}{16}}=$
$\small =\sqrt{\dfrac{6+3}{16}}=$
$\small =\sqrt{\dfrac{9}{16}}= \dfrac{3}{4}$